1999
DOI: 10.1007/s11906-999-0061-2
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-channel blockers and the progression of renal disease

Abstract: Effective blood pressure (BP) reduction is now generally recognized as a clinically proven strategy to retard the seemingly inexorable downhill progression of patients with diabetic and nondiabetic chronic renal disease. Although calcium-channel blockers (CCBs) are effective antihypertensive agents, the available experimental and clinical data are quite contradictory as to whether BP reduction achieved with CCBs provides the expected renoprotection. Blockade of the "L" type, voltage-gated Ca channels that medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Our results show that this provides smoothing in space and time that minimizes the cumulative error in regulation of downstream blood flow and glomerular capillary pressure. Given the importance of autoregulation in protecting the renal vasculature from hypertensive injury (20,21,34,70), synchronization of autoregulation is becoming an increasingly important aspect of RBF control. Certainly there is experimental evidence for frequency-and amplitude-modulation of MR by TGF (29,30,48,50,53,62,63) at levels from neighboring nephrons to whole kidney blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that this provides smoothing in space and time that minimizes the cumulative error in regulation of downstream blood flow and glomerular capillary pressure. Given the importance of autoregulation in protecting the renal vasculature from hypertensive injury (20,21,34,70), synchronization of autoregulation is becoming an increasingly important aspect of RBF control. Certainly there is experimental evidence for frequency-and amplitude-modulation of MR by TGF (29,30,48,50,53,62,63) at levels from neighboring nephrons to whole kidney blood flow.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, renal plasma flow is somewhat decreased by diuretics and beta-blockers. One concern expressed for calcium channel blockers (CCBs) is whether blood pressure reduction achieved with CCBs provides the expected renoprotection [3]. Blockade of the "L" type, voltage-gated Ca channels that mediate the BP reduction has been shown to concurrently impair renal autoregulatory responses of the preglomerular vasculature [4].…”
Section: Mechanisms Linking Hypertension Therapy Nephroprotection Amentioning
confidence: 99%
“…A large percentage of end-stage renal disease cases are directly attributable to the consequences of diabetes. Some authors [3,4] have suggested that the common use of calcium channel blockers has been responsible for higher rates of renal disease despite improved blood pressure control. Other authors [5] have pointed to thiazide diuretics as being permissive of nephrotoxicity through a failure to inhibit angiotensin II (Ang II) and indeed raising renin levels that induce Ang II production, as well as through mechanisms that increase serum uric acid levels.…”
Section: Introductionmentioning
confidence: 99%